A Case of a Young Patient with Nested Variant of Urothelial Carcinoma of the Bladder - Sano, Takanori (Hinyokika kiyo. Acta urologica Japonica, 2020)
A 26-year-old man visited our hospital with a complaint of macrohematuria. Cystoscopy revealed a nodular tumor around the right ureteral orifice. Transurethral resection of bladder tumor was performed, and the tumor was pathologically diagnosed as the nested variant of urothelial carcinoma (NVUC). Radical cystectomy and modified Studer orthotopic neobladder reconstruction were performed. The pathological stage was pT2a, pN2. The patient received 2 courses of adjuvant chemotherapy consisting of gemcitabine and cisplatin. The patient is currently free from disease at 31 months after the treatment. To our knowledge, this case report represents the youngest case of NVUC